Islamic Market Mechanism According to Abu Yusuf and His Willingness to the Panorama Market Mechanism Of Bengkulu City - Idwal B; Sahara Ratna Sari (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2021)
The Islamic Market Mechanism According to Abu Yusuf and its Relevance to the Panorama Market in Bengkulu City, the research method used in this study is library research, the research approach, and data collection techniques used are qualitative data (qualitative research) and documentation. The analysis technique used is inductive deductive, and descriptive. Based on the specific fission and style that applies to the character, the inductive method is better understood than general conclusions are drawn. The deductive method is collecting, analyzing, and researching general data to draw specific conclusions. The descriptive method is the regular description of all conceptions of the characters regarding the topic or research discussion. From the results of this study, it was found that the market and price mechanism according to Abu Yusuf is a practice that provides general problems (al-mashlahah al’-ammah), both from the producer (seller) and the buyer, while the relevance of the Islamic Market mechanism at the Panorama Market in Bengkulu City irrelevant and can not be fully implemented as the Islamic market mechanism according to the thought of Abu Yusuf.